Concurrent detection of autolysosome formation and lysosomal degradation by flow cytometry in a high-content screen for inducers of autophagy - Hundeshagen, Phillip; Hamacher-Brady, Anne; Eils, Roland; Brady, Nathan (BMC biology, 2011)
Autophagy mediates lysosomal degradation of cytosolic components. Recent work has associated autophagic dysfunction with pathologies, including cancer and cardiovascular disease. To date, the identification of clinically-applicable drugs that modulate autophagy has been hampered by the lack of standardized assays capable of precisely reporting autophagic activity.